The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/10473289.2006.10464504
|View full text |Cite
|
Sign up to set email alerts
|

Demolition of High-Rise Public Housing Increases Particulate Matter Air Pollution in Communities of High-Risk Asthmatics

Abstract: Public housing developments across the United States are being demolished, potentially increasing local concentrations of particulate matter (PM) in communities with high burdens of severe asthma. Little is known about the impact of demolition on local air quality. At three public housing developments in Chicago, IL, PM with an aerodynamic diameter Ͻ10 m (PM 10 ) and Ͻ2.5 m were measured before and during high-rise demolition. Additionally, size-selective sampling and real-time monitoring were concurrently per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 16 publications
(30 reference statements)
0
28
1
Order By: Relevance
“…All such building activities 46 are known to release significant amounts of coarse particles into the local 47 environment. For instance, Dorevitch et al (2006) found a 74% increase in PM 10 48 (particulate matter with 10 m aerodynamic diameter) concentrations 100 m 49 downwind of a high-rise building demolition site in Chicago, USA. Likewise, 50 Fuller et al (2002) showed that fugitive PM 10 emissions produced from building 51 works at Marylebone Road in London during September 1999 contributed to daily 52 mean PM 10 concentrations in excess of 50 g m -3 .…”
mentioning
confidence: 99%
“…All such building activities 46 are known to release significant amounts of coarse particles into the local 47 environment. For instance, Dorevitch et al (2006) found a 74% increase in PM 10 48 (particulate matter with 10 m aerodynamic diameter) concentrations 100 m 49 downwind of a high-rise building demolition site in Chicago, USA. Likewise, 50 Fuller et al (2002) showed that fugitive PM 10 emissions produced from building 51 works at Marylebone Road in London during September 1999 contributed to daily 52 mean PM 10 concentrations in excess of 50 g m -3 .…”
mentioning
confidence: 99%
“…For example, Dorevitch et al (2006) measured PM10 during the demolition of a reinforced concrete building and found 6h averaged concentrations up to about 10-times higher compared with predemolition levels which are background concentrations in this case. Likewise, Beck et al (2003) found ambient levels of PM10 to increase by between 8 and 3000-times during implosion of a building compared with pre-demolition levels, depending on the distance of measurement point from the source.…”
Section: Particle Mass Concentrationsmentioning
confidence: 77%
“…As a consequence, it is essential to determine the exposure levels of operatives involved in building refurbishment as well as understanding the It has now been established that various size of particles arising from vehicle exhaust and non-vehicle exhaust sources enhance their concentrations in certain areas (Dall'Osto et al, 2011;Hopke et al, 1980;Kumar et al, 2010Kumar et al, , 2011bKumar et al, , 2013b. A few studies have also reported the particle number and mass emissions arising from the demolition of buildings and transport structures (Dorevitch et al, 2006;Hansen et al, 2008), concrete recycling and road works (Fuller et al, 2002;Fuller and Green, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects were recruited by community asthma educators in three Chicago public housing developments in which high rise demolition was taking place (Dorevitch et al, 2006 Eligible subjects had physician-diagnosed asthma, or were non-asthmatic family members of asthmatic subjects. Exclusion criteria were smoking, age less than 8 years, lung disease other than asthma, or daily use of oral corticosteroids.…”
Section: Subjectsmentioning
confidence: 99%